2018
DOI: 10.1021/acs.est.8b01611
|View full text |Cite
|
Sign up to set email alerts
|

Quality Criteria for the Analysis of Microplastic in Biota Samples: A Critical Review

Abstract: Data on ingestion of microplastics by marine biota are quintessential for monitoring and risk assessment of microplastics in the environment. Current studies, however, portray a wide spread in results on the occurrence of microplastic ingestion, highlighting a lack of comparability of results, which might be attributed to a lack of standardization of methods. We critically review and evaluate recent microplastic ingestion studies in aquatic biota, propose a quality assessment method for such studies, and apply… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
311
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 428 publications
(319 citation statements)
references
References 86 publications
5
311
1
2
Order By: Relevance
“…A key challenge, however, relates to limitations in analytical capability. Several reviews summarizing the advantages and disadvantages of the various analytical methods have been published (Hidalgo‐Ruz et al 2012; Rocha‐Santos and Duarte 2015; Lusher et al 2017; Hermsen et al 2018). There is clearly a need for standardized quantitative methods.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A key challenge, however, relates to limitations in analytical capability. Several reviews summarizing the advantages and disadvantages of the various analytical methods have been published (Hidalgo‐Ruz et al 2012; Rocha‐Santos and Duarte 2015; Lusher et al 2017; Hermsen et al 2018). There is clearly a need for standardized quantitative methods.…”
Section: Resultsmentioning
confidence: 99%
“…The literature data on ingestion of microplastic particles to include in the present review was initially based on the reference lists reported in several robust reviews recently published for organisms at all levels of biological organization (Schuyler et al 2014; Deudero and Alomar 2015; Lusher et al 2017; Poeta et al 2017; Burns and Boxall 2018; Foley et al 2018; Fossi et al 2018; Hermsen et al 2018; Battisti et al 2019; Botterell et al 2019; Triebskorn et al 2019; Wang et al 2019). The initial list was further complemented by identification of other studies, using a range of methods.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations